"Ruxia" and "Ruxianos" in the romances of chivalry written by Feliciano de Silva - Setkowicz, Katarzyna (Eslavística Complutense, 2015)
In this article, we examine the way in which Feliciano de Silva uses an authentic toponym Rus (Ruxia) in constructing the world presented in his romances of chivalry. As it is shown, Feliciano de Silva only partially follows the trend previously established by Garci Rodriguez de Montalvo, who in his works outlines a clear opposition between the Christian world of knight-errant and the evil and wicked paganism. The author from Ciudad Rodrigo, in order to make a reference to the glory of medieval Constantinople, goes back to the days of the Byzantine-Ruthenian conflict that he creatively uses in three books of Florisel de Niquea. Ruxia, one of the main opponents of the Greek family, is depicted as a pagan military power led by brave, but also overwhelmed with lust, immoral and cruel rulers.